2002
DOI: 10.1128/aac.46.11.3401-3405.2002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Chromosome-Borne Expanded-Spectrum Class A β-Lactamase from Erwinia persicina

Abstract: From whole-cell DNA of an enterobacterial Erwinia persicina reference strain that displayed a penicillinaserelated antibiotic-resistant phenotype, a ␤-lactamase gene was cloned and expressed in Escherichia coli. It encoded a clavulanic-acid-inhibited Ambler class A ␤-lactamase, ERP-1, with a pI value of 8.1 and a relative molecular mass of ca. 28 kDa. ERP-1 shared 45 to 50% amino acid identity with the most closely related enzymes, the chromosomally encoded enzymes from Citrobacter koseri, Kluyvera ascorbata, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
1
14
0
1
Order By: Relevance
“…In fact, PLA-1 had stronger hydrolytic activity than TEM-1 not only against penicillins but also against cephalosporins, including the extended-spectrum cephalosporins, and aztreonam (21). The catalytic efficiency of PLA-1 against cefotaxime was similar to the efficiencies observed for the chromosomal ␤-lactamases of Proteus penneri (16), Rahnella aquatilis (3), and E. persicina (35), whereas the efficiency against cefepime, which was rarely tested in the previous studies, was significantly higher than that observed for R. aquatilis (3) and resembled that displayed by plasmid-mediated CTX-M type ␤-lactamases such as CTX-M-18 (30). As the extended substrate profile of class A ␤-lactamases has previously been shown to be related to specific amino acid residues at defined positions, we analyzed the protein sequences of the ␤-lactamases of Raoutella spp.…”
Section: Discussionsupporting
confidence: 48%
“…In fact, PLA-1 had stronger hydrolytic activity than TEM-1 not only against penicillins but also against cephalosporins, including the extended-spectrum cephalosporins, and aztreonam (21). The catalytic efficiency of PLA-1 against cefotaxime was similar to the efficiencies observed for the chromosomal ␤-lactamases of Proteus penneri (16), Rahnella aquatilis (3), and E. persicina (35), whereas the efficiency against cefepime, which was rarely tested in the previous studies, was significantly higher than that observed for R. aquatilis (3) and resembled that displayed by plasmid-mediated CTX-M type ␤-lactamases such as CTX-M-18 (30). As the extended substrate profile of class A ␤-lactamases has previously been shown to be related to specific amino acid residues at defined positions, we analyzed the protein sequences of the ␤-lactamases of Raoutella spp.…”
Section: Discussionsupporting
confidence: 48%
“…The tiny ESBL2 cluster comprises three representative enzymes (ERP-1, DES-1, and BES-1) and a single putative enzyme (Desulfovibrio desulfuricans). ERP-1 (from Erwinia persicina) was the first enterobacterial extended-spectrum ␤-lactamase to be shown to be pathogenic to plants (37). The kinetic parameters of the ERP-1 enzyme place it in group 2be (Table 1).…”
Section: Toca P Vulgaris R Aquatilis and S Fonticola)mentioning
confidence: 99%
“…As observed in TEM-1, TEM-2, LEN-1, OXY-1, and OXY-2 ␤-lactamases, an Ala residue was found in position 237. On the other hand, some TEM-type and SHV-type extended-spectrum ␤-lactamases, CTX-M variants, and chromosome-encoded enzymes of Kluyvera ascorbata (KLUA-1), Kluyvera cryocrescens (KLUC-1), Kluyvera georgiana (KLUG-1), P. vulgaris (RO104), S. fonticola (CUV), C. sedlakii (Sed-1), Citrobacter diversus (CdiA), R. aquatilis (RHAN-1), and Erwinia persinica (ERP-1) possess a Ser residue in this position, which is involved in extended activity towards cefuroxime and extended-broad-spectrum cephalosporins (2,9,12,19,20,21,23,28). Moreover, HER-1 possess two cysteines in positions 77 and 123 as in TEM and SHV ␤-lactamases and as in few others; a disulfide bridge is also likely to be present in the E. hermannii ␤-lactamase.…”
mentioning
confidence: 99%